2020
DOI: 10.11622/smedj.2019099
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing quality of life of Asian breast cancer patients and their caregivers at diagnosis: perceived medical and psychosocial needs

Abstract: Online first papers have undergone full scientific review and copyediting, but have not been typeset or proofread. To cite this article, use the DOIs number provided. Mandatory typesetting and proofreading will commence with regular print and online publication of the online first papers of the SMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Most of the high-need items in the "treatment" subscale relate to side effects. A previous survey (Chow et al, 2020) of supportive needs in women with breast cancer in Singapore similarly reported a high need for information related to treatment side effects. Chow et al reported that information about treatment and treatment options (including side effects) and information about treatment for side effects ranked among the top three needs of patients with breast cancer and their caregivers at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the high-need items in the "treatment" subscale relate to side effects. A previous survey (Chow et al, 2020) of supportive needs in women with breast cancer in Singapore similarly reported a high need for information related to treatment side effects. Chow et al reported that information about treatment and treatment options (including side effects) and information about treatment for side effects ranked among the top three needs of patients with breast cancer and their caregivers at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated information needs specifically in women with breast cancer (Chow et al, 2020;Lai et al, 2019;Sheehy et al, 2018). In a study of information needs in Asian women with breast cancer, Chow et al (2020) reported that prompt information about treatment and treatment options, including side effects, was one of the top three extremely important needs at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to Chinese patients having more unmet supportive care needs based on a study at an outpatient oncology clinic in a tertiary hospital in Malaysia [ 31 ]. Additionally, a prospective longitudinal observational study completed at a regional hospital in Singapore found that ethnicity was a significant determinant of HQOL in the domains of role limitations due to emotional problems and social functioning on the Short Form-36 health survey scale [ 32 ]. It is also possible that this may be due to Malays displaying a higher mental health component than the Chinese, which has been shown in a local multi-ethnic study on chronic illnesses [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breasts are considered part of the female identity, representing femininity, sex, beauty, and motherhood and empowering them to breastfeed their babies (Savitri, 2015). Losing a breast can also cause self-concept obstacles, such as changes in body image, loss of self-identity, changes in social roles, changes in self-ideal, and loss of self-esteem (Campbell-Enns & Woodgate, 2015;Chow et al, 2020;Heidari & Ghodusi, 2015;Lovelace et al, 2019). Negative self-concepts can easily lead to stress and depression (Aguado Loi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%